La Inteligencia Artificial como herramienta para la elaboración de productos sonoros (cuñas, podcast, cápsulas) para radios analógicas y digitales en la región sur de Ecuador. - Maza Camacho, Jackeline Alexandra (2023)
Artificial Intelligence (AI) is currently a significant part of some media that are interested in the innovation and creativity of their content, thus applying it in the automation of information, sound production and various journalistic routines. In order to deepen this relationship, the following objectives are formulated: To analyze artificial intelligence as a tool for the elaboration of sound products (spots, podcasts, capsules) for analog and digital radios in the southern region of Ecuador; To identify software and online platforms for the production with Artificial Intelligence; To elaborate sound products with Artificial Intelligence for analog and digital radios; Establish the experiences of users, consumers and listeners of sound products generated with Artificial Intelligence and human voice; Determine the feasibility of implementing sound products built from Artificial Intelligence as a new resource for the production of sound in radio; Propose a user manual for the creation of sound products with Artificial Intelligence on three platforms. A mixed methodology was used, on the one hand, surveys were conducted and applied at the Universidad Nacional de Loja, Universidad Técnica Particular de Loja and Universidad Técnica de Machala. On the other hand, the research was complemented with interviews to AI experts and culminated with an observation sheet to identify the software and online platforms to build the sound pieces. The results showed that most people like this type of sound products, which encourages the use of programs that incorporate artificial voices to the sound content. It is concluded that the fusion of artificial intelligence and radio is projected to be one of the strongest resources that can change the sound generation industry. Keywords: automation, artificial intelligence, radio, artificial voices.